A behavioural finance explanation of speculative bubbles: evidence from the bitcoin price development - Koehn, Maximilian-Benedikt; Cekuls, Andrejs (University of Latvia, 2019)
In 2008 a group of programmers, alias Satoshi Nakamoto, introduced bitcoin. Bitcoin is a cryptocurrency or virtual money derived from mathematical cryptography and is conceived as an alternative to government authorised currency. The founder anticipated, through bitcoin’s construction and his digital mining processes, that bitcoin prices would be relatively stable. However, the recent bitcoin price decline proves that bitcoin is extraordinarily volatile and is not that stable as hoped. Although some scientists have already shown that the fundamental value of bitcoin is zero, the price of bitcoin has reached over 19.000$ in December 2018. Since then, bitcoin prices dropped nearly 70% from their peak value and showed in addition to that the typical trends of a speculative bubble. Hyman Minsky and Charles Kindleberger discussed three different patterns of speculative bubbles. One is when price rises in an accelerating way and then crashes very sharply after reaching its peak. Another is when the price rises and is followed by a more similar decline after reaching its peak. The third is when the price rises to a peak, which is then followed by a period of gradual decline known as the period of financial distress, to be followed by a much sharper crash at some later time. One of the key findings of this study is that all these three patterns occurred during 2017-18 for the bitcoin price. Therefore, the purpose of this paper is to analyse the historical bitcoin prices in context with the typical five-step characteristics of a speculative bubble. Furthermore, each phase of a speculative bubble is explained by a behavioural finance approach and answer the price development of this cryptocurrency. The result is frightening, bitcoin can be seen as a perfect textbook example of a speculative bubble.
Keywords: Bitcoin; Cryptocurrencies; Bubbles; Behavioural Finance; Volatility; Research Subject Categories::SOCIAL SCIENCES::Business and economics